Should we treat pediatric radiologically isolated syndrome? An 18-year follow-up case report - Barbuti, Elena; Nistri, Riccardo; Ianniello, Antonio; Pozzilli, Carlo; Ruggieri, Serena (Frontiers in Neurology, 2023)
Background: Radiologically isolated syndrome (RIS) describes asymptomatic individuals with incidental radiologic abnormalities suggestive of Multiple sclerosis (MS). Much of RIS literature is about adult-onset cases. Treatment of RIS is controversial, especially in paediatric age, but early treatment in selected patients might improve long-term outcomes. Case presentation: We report a single RIS patient followed-up for 18 years in our MS Center. At first, she was only monitored with follow-up MRIs. Then, as the lesion load increased, she was treated with a first-line disease modifying treatment (DMT) reaching MRI stability. Conclusions: This report highlights how treatment can be an appropriate choice in paediatric forms of RIS.